Frequency of abnormal and stereotypic behaviors in urban police patrolling horses: a continuous 48-hour study - Zuluaga, Angélica M.; Mira, Alejandro; Sánchez, José L.; Martínez A., José R. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Abnormal and stereotypic behaviors in horses have been widely studied around the world and different epidemiological situations have been described for behavioral disturbances. Objective: To determine the frequency of abnormal and stereotypic behaviors in a population of police patrolling horses. Additionally, to establish chronic stress levels in the population of interest. Methods: Twenty police horses were evaluated. The animals went through 48 hours of continuous observation to record the frequency of normal, abnormal, and stereotypic behaviors. Cortisol index (CI) was calculated for all the subjects. Results: A 65% of the horses expressed behavioral disturbances, with 55% corresponding to stereotypies. The abnormal behaviors consisted on wood chewing, pawing, and bed eating. Stereotypic behaviors were weaving, stall walking, and aerophagia (crib-biting or wind sucking). According to the CI, 13 horses were under chronic stress (CI < 0.30). Conclusion: High level of chronic stress, expressed as abnormal and stereotypic behaviors, was observed in the horses.